1986
DOI: 10.1002/cyto.990070504
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of an EMBL‐3 phage library containing partially digested human chromosome 21‐specific DNA inserts (15–20 kb)

Abstract: In the mouse-human hybrid cell line SCC 16-5, chromosome 21 is the only human chromosome present. Fractions highly enriched for this chromosome were obtained by applying the chromosome velocity sedimentation technique to this cell line, DNA prepared from these chromosomal fractions was partially digested with Mbo I, size fractionated on an NaCl gradient, and cloned in the EMBL-3 phage vector.The phage library thus prepared was highly enriched for human chromosome 21-specific recombinant DNA sequences 15-20 kb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Cells and Cell Culture-SCC16 -5, a murine fibroblast cell line that contains a single copy of human chromosome 21 (33), and Colo-205, a human adenocarcinoma cell line, were cultured as described previously (26,34).…”
Section: Methodsmentioning
confidence: 99%
“…Cells and Cell Culture-SCC16 -5, a murine fibroblast cell line that contains a single copy of human chromosome 21 (33), and Colo-205, a human adenocarcinoma cell line, were cultured as described previously (26,34).…”
Section: Methodsmentioning
confidence: 99%
“…The murine cell line SCC-16-5 (SCC; provided by R. Schreiber, Washington University, St. Louis, Mo.) is a human-murine L-cell somatic cell hybrid which contains a single copy of human chromosome 21 (27). It was grown in Dulbecco's modified Eagle medium with 10% fetal calf serum, 2 mM L-glutamine, 50 U of penicillin per ml, and 50 ,ug of streptomycin per ml.…”
Section: Methodsmentioning
confidence: 99%
“…2 It is interesting that the requirement for the corresponding tyrosine residue of human IFNGR1, Tyr 440 , appears to be different: in primary human fibroblasts lacking IFNGR1 and reconstituted with the Y440F mutant, the expression of ISGs in response to IFN␥ was substantial, although the antiviral effect was inhibited. 3 The hybrid murine fibroblast cell line SCC16-5, containing a single copy of human chromosome 21 encoding human IFNGR2, was used initially to characterize human IF-NGR1 (49,50). The expression of various mutants of IFNGR1 in these cells revealed that Tyr 440 is required for STAT1 activation and antiviral activity (29,51).…”
Section: Contribution Of Specific Tyrosinementioning
confidence: 99%